Generic Symmetries of the Laurent Extension of Quantum Plane - Sinel'shchikov, S. (Журнал математической физики, анализа, геометрии, 2015)
A list of generic Uq (sl)-module algebra structures on the Laurent polynomial algebra over the quantum plane with uncountably many isomorphism classes is produced. Also, a complete list of these structures is presented in which the action of Cartan generator of Uq (sl) is not reduced to multiplying x and y (the generators of quantum plane) by constants. Построен список структур Uq (sl2) -модульной алгебры общего положения на алгебре полиномов Лорана над квантовой плоскостью, содержащий несчетное количество классов изоморфизма. Предъявлен полный список подобных структур, в которых действие картановской образующей квантовой универсальной обертывающей Uq (sl2) не сводится к умножению x и y (образующих квантовой плоскости) на константы.